2013
DOI: 10.1002/14651858.cd001449.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Drugs for treatment of very high blood pressure during pregnancy

Abstract: Any e ect on a comparative improvement in control of blood pressure would be of far greater clinical importance if it was reflected in comparative improvements in other more substantive outcomes, such as stroke, serious maternal morbidity and perinatal Drugs for treatment of very high blood pressure during pregnancy (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
2
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(136 citation statements)
references
References 80 publications
5
119
2
10
Order By: Relevance
“…Kemudian, dipantau respons terhadap pengobatan yaitu dengan memastikan terjadi penurunan tekanan darah, mengidentifikasi efek samping bagi ibu dan janin, memodifikasi pengobatan sesuai dengan respons, pertimbangkan untuk menggunakan < 500 ml cairan kristaloid sebelum atau pada saat yang sama dengan dosis pertama hydralazine yang bertujuan untuk menjaga tekanan darah di bawah 150/100 mmHg. 19 Pengaruh tekanan darah sistolik terhadap kematian pada ibu pre-eklampsia tidak terlihat dengan jelas. Beberapa hasil penelitian masih menunjukkan hasil yang kontradiktif.…”
Section: Pembahasanunclassified
“…Kemudian, dipantau respons terhadap pengobatan yaitu dengan memastikan terjadi penurunan tekanan darah, mengidentifikasi efek samping bagi ibu dan janin, memodifikasi pengobatan sesuai dengan respons, pertimbangkan untuk menggunakan < 500 ml cairan kristaloid sebelum atau pada saat yang sama dengan dosis pertama hydralazine yang bertujuan untuk menjaga tekanan darah di bawah 150/100 mmHg. 19 Pengaruh tekanan darah sistolik terhadap kematian pada ibu pre-eklampsia tidak terlihat dengan jelas. Beberapa hasil penelitian masih menunjukkan hasil yang kontradiktif.…”
Section: Pembahasanunclassified
“…This is not recommended based on the results of trials. 27 Although observational studies suggest that there may be some transient lowering of BP 30 minutes after administration of 2 to 5 g of IV magnesium sulphate, usually in patients with preeclampsia, a sustained antihypertensive effect cannot be anticipated. [28][29][30][31] The majority of these women (approximately 75%) will require antihypertensive therapy even while on magnesium sulphate and approximately 50% will require rapid-acting medication to lower BP acutely.…”
Section: Geographica and Income Distribution Of Identi Ed Emls In 14mentioning
confidence: 99%
“…They concluded that until better evidence is available, the choice of antihypertensive should depend on what is known about adverse drug effects and how familiar the clinician is with use of a particular drug. 5 Tabasi et al also found the two drugs to be similar in the control of hypertension. 6 In study by De Pasquale et al the number of doses to achieve control of blood pressure was 1.4 and 1.3 in Hydralazine and Labetalol groups respectively and the difference was not significant (p=0.25).…”
Section: Discussionmentioning
confidence: 95%